2009
DOI: 10.1128/aac.01057-08
|View full text |Cite
|
Sign up to set email alerts
|

Virologic Failure in Therapy-Naïve Subjects on Aplaviroc plus Lopinavir-Ritonavir: Detection of Aplaviroc Resistance Requires Clonal Analysis of Envelope

Abstract: The CCR100136 (EPIC) study evaluated the antiviral activity of the novel CCR5 entry inhibitor aplaviroc in combination with lopinavir-ritonavir in drug-naïve human immunodeficiency virus type 1-infected subjects. Although the trial was stopped prematurely due to idiosyncratic hepatotoxicity, 11 subjects met the protocoldefined virologic failure criteria. Clonal analyses of the viral envelope tropism, aplaviroc susceptibility, and env sequencing were performed on plasma at day 1 and at the time of virologic fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 30 publications
(27 reference statements)
5
35
0
Order By: Relevance
“…Thus, there is some variability in the relative importance of the CCR5 NЈ-terminal domain and ECL2 in supporting infection by different HIV-1 strains (41). This underlying plas- ticity can lead to rare, unexpected outcomes: we identified a patient whose virus exhibited baseline resistance to all CCR5 antagonists tested, which likely contributed to this individual's subsequent virologic failure on an antiviral regimen that included aplaviroc (21,48). This finding poses two central questions: by what mechanism(s) does resistance to CCR5 antagonists occur, and what are the implications of drug resistance for viral tropism?…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, there is some variability in the relative importance of the CCR5 NЈ-terminal domain and ECL2 in supporting infection by different HIV-1 strains (41). This underlying plas- ticity can lead to rare, unexpected outcomes: we identified a patient whose virus exhibited baseline resistance to all CCR5 antagonists tested, which likely contributed to this individual's subsequent virologic failure on an antiviral regimen that included aplaviroc (21,48). This finding poses two central questions: by what mechanism(s) does resistance to CCR5 antagonists occur, and what are the implications of drug resistance for viral tropism?…”
Section: Discussionmentioning
confidence: 90%
“…Resistant viruses that utilize drug-bound CCR5 have been identified following in vitro passaging with multiple CCR5 antagonists (1,2,22,33,36,51,56). Recently, we identified a panel of viral Envs able to use aplaviroc (APL)-bound CCR5 that were isolated from a patient (21,48). The Envs from this patient were cross resistant to the CCR5 antagonists AD101, TAK779, SCH-C, and maraviroc.…”
mentioning
confidence: 99%
“…These data are slightly different than the initial characterization of Envs from P5, in which the magnitude of APL resistance was greater in CCR5-expressing cells, and some clones were able to utilize CXCR4 for entry. 26 One explanation for these differences is that the pseudoviruses were produced separately using different cloning vectors and may have different characteristics. Additionally, although both sets of assays were performed on the same cell line, namely U87=CD4=CCR5, the CD4 and CCR5 expression levels may have been different in cells cultured in two separate laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, viruses passaged in the presence of increasing concentrations of CCR5 antagonists have evolved to utilize drug-bound CCR5 for entry, and coreceptor switching is rarely observed. 34 The initial characterization of viruses from this patient by Kitrinos and colleagues 26 indicated that some Envs used only CCR5 to mediate infection, whereas others could also use CXCR4 to a limited extent, with relative light units close to the threshold of the assay employed. In this study, we examined the tropism of the cloned envs by using pseudotyped viruses on cell lines expressing CD4 and either CCR5 or CXCR4.…”
Section: Patient-derived Envs Utilize Ccr5 For Entrymentioning
confidence: 99%
See 1 more Smart Citation